Adolescent Alcohol Use Before and After the High School Transition. (2nd May 2015) - Burdzovic Andreas, Jasmina; Jackson, Kristina M.
<x xml:space="preserve">Abstract</x> Background An important question is whether the high school (HS) entry is a critical developmental event associated with escalation of alcohol use. This study examined trajectories of adolescent alcohol use as a function of a normative developmental event—the HS entry. In addition, given that at‐risk youth may be particularly vulnerable to the stress associated with this transition, we examined how these alcohol use trajectories may be shaped by a measure of early behavioral risk, early adolescent delinquency. Methods Participants included 891 twelve‐year‐olds from the prospective National Longitudinal Survey of Youth 1997 for whom relevant longitudinal school data were available (51.2% boys; 61.4% White). Results Alcohol use after HS entry increased at a significantly greater rate than did use during the middle school years, even after accounting for students' age at transition. In addition, early delinquency emerged as a risk factor such that differences in alcohol use existed prior to the transition. That is, children with early delinquency characteristics displayed more rapid progression in alcohol use, but this effect was evident only during middle school. Conclusions HS entry appears to be a critical developmental event associated with increased social risk for greater alcohol use that goes beyond the simple maturational (i.e., aging) factors. Youth with behavioral problems appears to be at greater risk in middle school, in contrast to lower risk youth for whom HS entry may be a more critical event, in part because HS may be a less restrictive environment and/or because alcohol use becomes more normative at that time. Adolescent substance use may be described as a series of distinct developmental stages that closely correspond to school transitions and suggest a critical period for targeted intervention that may differ as a function of preexisting risk.